Audit Committee Influence on Financial Performance: Evidence from Indonesia’s Healthcare Sector (2019-2023) - Tiara Syah Rani; Payamta Payamta (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This research seeks to analyze the impact of audit committee features on the financial performance of healthcare entities listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The analyzed parameters include audit committee size, independence of the audit committee, skill of the audit committee, and frequency of audit committee meetings. Return on Assets (ROA) serves as a critical performance metric, with business size and the COVID-19 criteria accounted for. This study utilizes a quantitative approach using panel data regression analysis on a sample chosen by purposive sampling methods. This research is driven by notable variations in Return on Assets (ROA) throughout the healthcare industry and a financial reporting controversy concerning PT Indofarma Tbk. The findings indicate a substantial and noteworthy impact of audit committee size and independence on financial performance. In contrast, the experience of the audit committee and the frequency of meetings have no substantial influence. These results highlight the need of harmonizing structural characteristics and efficient supervision within the audit committee for good corporate governance. The research provides actionable insights for regulators and corporate management in enhancing the functions of audit committees.